Processamento e caracterização de condutores de íons O2- a partir de cerâmicas BIMEVOX - Biz, Helder (Universidade Federal de São Carlos, 2005)
In this work, the processing of BIMEVOX family ceramics (ME-doped bismuth vanadate, ME =Cu2+, Fe3+ and Ti4+), obtained by precursor oxides fusion method was studied. The resulting powders were valued by X ray diffraction, atomic emission spectrometry, scanning and transmission electronic microscopy, and analyzed by particle size distribution. The obtained results showed the oxides fusion method promoted the formation of the interest phases, with the desired content of dopants. The powders presented a majority crystalline portion and a residual vitreous phase, which can be responsible for the relatively high final densities (above 95%) of the sintered samples, reached at lower temperatures (750 ºC for BICUVOX and 800 ºC for BIFEVOX and BITIVOX) and shorter firing times (4 hours), if compared with some literature data. The microstructure of samples was revealed without any superficial treatment or etching (thermal or chemical), but there is not an explanation for this phenomenon yet. The grains presented a mean size small enough (about 3 µm) to promote a reproducibility of the electrical conductivity over a heatingcooling thermal cycle, at the temperature range valued (150 450 ºC). Electrical conductivity was not significantly influenced by the pO2 not even for the final density of the samples, and the activation energy values for the conduction presented small difference. Electrical measurements indicated the presence of order-disorder transformations in between 450-500 °C, which were showed up through the change of the slope in the conductivity-temperature curves. According to the carried out tests in prototypes, in spite of unsuitability of BIMEVOX materials studied for the application in melted metals at 1600 °C (due low melting point of these ceramics), they can be possibly applied as gas sensors in ambient of lower temperatures.
Processing and characterization of O2- ion conductors from BIMEVOX ceramics
Keywords: Cerâmica; BIMEVOX; Processamento cerâmico; Reação de fusão de óxidos; Sensores de oxigênio; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA